A nitrogen-containing compound solid solution photocatalyst, a preparation method therefor, and an application thereof

CN117983269BActive Publication Date: 2026-10-20DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211338766.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-28
Publication Date
2026-10-20
Estimated Expiration
2042-10-28

AI Technical Summary

Technical Problem

然而,对于氮掺杂氧化物-(氮)氧化物固溶体,目前的研究仅限于钙钛矿型结构(ABO3)的中A位点的变化,如NaxLa1-xTaO1+2xN2-2x、Sr1-xCaxTaO2N

Benefits of technology

[0028]①本发明合成过程简单易操作,易于大面积推广应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117983269B_ABST
    Figure CN117983269B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of nitrogen-containing compound solid solution photocatalyst and its preparation method and application, belong to catalytic material technical field.TaCl5 is dissolved in methanol solution, add ethylene glycol and citric acid, then add Ba (NO3) 3 And MgCO3, heating treatment is carried out, temperature is raised to reflux, sol gel treatment is carried out, calcination treatment is carried out to remove organic carbon, nitrogenization treatment under ammonia atmosphere is carried out, nitrogen-containing compound solid solution is obtained, then by loading noble metal, perovskite structure nitrogen-containing compound solid solution photocatalyst is obtained.The synthesis process of the present application is simple and easy to operate, easy to large-area popularization and application, catalyst yield is high, chemical property is stable, with absorption band edge between 560nm and 650nm adjustable, with potential application value in photocatalytic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a nitrogen-containing compound solid solution photocatalyst, its preparation method and application, belonging to the field of catalytic materials technology. Background Technology

[0002] Achieving complete photocatalytic splitting of water into H2 and O2 using inorganic semiconductor photocatalysts is one of the ideal methods for solving the energy crisis and environmental problems. To this end, a large number of ultraviolet-responsive semiconductor materials have been developed. However, these materials have wide band gaps and low utilization of visible light in the solar energy spectrum. To effectively utilize solar energy, the development of semiconductor materials with broad spectral responses is imperative. Among the many developed visible-light-responsive semiconductor materials (metal oxides, metal oxyacid salts, metal / non-metal doped oxides, (oxy)nitrides, (oxy)sulfides, halide oxides, etc.), (oxy)nitrides have attracted widespread attention due to their broad visible light absorption and suitable conduction / valence band positions.

[0003] However, expanding the absorption range reduces the driving force for charge separation. While the contradiction between these two factors is irreconcilable, a balance can be achieved by adjusting the degree of their mutual constraint, allowing the semiconductor material to simultaneously possess a wide light absorption range and a large driving force. Among strategies for controlling the light absorption range and driving force, the formation of solid solutions allows for the simultaneous manipulation of the conduction band and valence band positions, providing the optimal solution for balancing light absorption and driving force. Currently, oxide-oxide solid solutions (β-AgAl) have been developed. 1-x Ga x O2, (AgNbO3) 1-x (SrTiO3) x ), oxide-nitride solid solution ((Ga 1- x Zn x (N) 1-x O x (BaZrO3-BaTaO2N) and sulfide-sulfide solid solutions ((AgIn)) x Zn2(1-x)S2, ZnS-GuInS2-AgInS2, etc. However, for nitrogen-doped oxide-(nitrogen)oxide solid solutions, current research is limited to variations in the A-site of the perovskite-type structure (ABO3), such as Na... x La 1-x TaO 1+2x N 2-2x Sr1-xCa x TaO2N. Therefore, it is essential to synthesize novel tunable solid solutions targeting the B sites in ABO3-type perovskite structures. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a perovskite-structured nitrogen-containing compound solid solution photocatalyst, its preparation method, and its application. [The invention involves] using Mg... 2+ Replaces the Ta at the B site in the ABO3 structure of BaTaO2N 5+ The solid solution catalyst exhibited excellent photocatalytic activity in both the photocatalytic water splitting half-reaction and the "Z" mechanism complete water splitting for hydrogen production. The heterogeneous photocatalytic experiments demonstrate that the perovskite-type nitrogen-containing compound solid solution involved in this invention has promising applications in the field of photocatalysis.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows:

[0006] This invention provides a nitrogen-containing compound solid solution photocatalyst, the method comprising the following steps:

[0007] (1) Dissolve TaCl5 in methanol solution, add ethylene glycol and citric acid, and make sure they are fully dissolved;

[0008] (2) Add Ba(NO3)3 and MgCO3 to the transparent solution obtained in step (1) and let them dissolve completely;

[0009] (3) Heat the solution obtained in step (2) under reflux;

[0010] (4) Heat the solution obtained in step (3) to perform sol-gelation;

[0011] (5) The solid powder obtained in step (4) is calcined to remove organic carbon and obtain an oxide precursor.

[0012] (6) The oxide precursor obtained in step (5) is subjected to nitriding treatment under an ammonia atmosphere to obtain a nitrogen-containing compound solid solution;

[0013] (7) The nitrogen-containing compound solid solution obtained in step (6) is loaded with noble metal to obtain a perovskite-structured nitrogen-containing compound solid solution photocatalyst.

[0014] In the above technical solution, the molar ratio of TaCl5, ethylene glycol and citric acid in step (1) is 1:15:60.

[0015] In the above technical solution, further, the molar ratio of Ba(NO3)3, MgCO3 and TaCl5 in step (2) is 1:0.05~0.4:0.6~0.95.

[0016] In the above technical solution, the reflux temperature in step (3) is 100-200℃ and the reflux time is 3-10h.

[0017] In the above technical solution, the heating temperature in step (4) is 250-400℃ and the heating time is 0.1-2h.

[0018] In the above technical solution, the roasting temperature in step (5) is 500-750℃ and the roasting time is 0.5-2h.

[0019] In the above technical solution, further, in step (6), the heating rate of the nitriding treatment is 5℃ / min, the ammonia flow rate is 100~250mL / min, the nitriding treatment temperature is 900~950℃, and the time is 6~10h.

[0020] In the above technical solution, the precious metal in step (7) further includes at least one of Ru, Rh, Pd, Ag, Ir, Pt, and Au, and the loading of the precious metal is 0.01 to 5 wt%.

[0021] The method of carrying precious metals is as follows:

[0022] (1) Disperse nitrogen-containing compound solid solution powder in a solution containing noble metal precursor, disperse by ultrasonication, and then evaporate to dryness in a water bath;

[0023] (2) Reduce at 100-400℃ for 0.5-3.0h under a hydrogen gas flow, or calcine at 100-500℃ for 0.5-4.0h under a nitrogen or argon inert atmosphere.

[0024] In the nitrogen-containing compound solid solution photocatalyst prepared by the above method, the absorption band edge of the nitrogen-containing compound solid solution can be continuously adjusted between 550 nm and 650 nm.

[0025] The second aspect of the present invention provides an application of the above-mentioned nitrogen-containing compound solid solution photocatalyst in the photocatalytic hydrogen production reaction, wherein one or more of lactic acid, sodium sulfide, ascorbic acid, formic acid, methanol, and triethanolamine are used as hole sacrificial reagents and dispersed together with the photocatalyst powder in H2O, and the H2O is decomposed by light to produce hydrogen.

[0026] A third aspect of this invention provides the application of the above-mentioned nitrogen-containing compound solid solution photocatalyst in the photocatalytic "Z" mechanism of total water splitting for hydrogen production, using IO3... - / I - Fe 3+ / 2+ [Fe(CN)6] 3- / 4- One or more of these components are used as redox couples and dispersed together with photocatalyst powder in H2O. The H2O is then decomposed by light to produce hydrogen and oxygen.

[0027] The beneficial effects of this invention are as follows:

[0028] ① The synthesis process of this invention is simple and easy to operate, and it is easy to promote and apply on a large scale.

[0029] ②The catalyst synthesized in this invention has high yield and stable chemical properties.

[0030] ③ The catalyst synthesized in this invention has an adjustable absorption band edge between 560 nm and 650 nm, and has potential application value in photocatalytic reactions. Attached Figure Description

[0031] Figure 1 This is a characterization diagram of the sample from Example 1, where a represents 0.9 BaMg. 1 / 3 Ta 2 / 3 O 3-y N y XRD pattern of 0.1 BaTaO2N powder, b is 0.9 BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.1 BaTaO2N powder UV-Vis absorption spectrum;

[0032] Figure 2 This is a characterization diagram of the sample from Example 2, where a represents 0.75 BaMg. 1 / 3 Ta 2 / 3 O 3-y N y XRD pattern of 0.25BaTaO2N powder, b is 0.75BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.25 BaTaO2N powder UV-Vis absorption spectrum;

[0033] Figure 3 This is a characterization diagram of the sample from Example 3, where a represents 0.6 BaMg. 1 / 3 Ta 2 / 3 O 3-y N y XRD pattern of 0.4BaTaO2N powder, b is 0.6BaMg 1 / 3 Ta 2 / 3 O 3-y N y UV-Vis absorption spectrum of 0.4BaTaO2N powder, c = 0.6BaMg 1 / 3 Ta 2 / 3 O 3- y N y Scanning electron microscope image of -0.4 BaTaO2N powder;

[0034] Figure 4This is a characterization diagram of the sample from Example 4, where a represents 0.3 BaMg. 1 / 3 Ta 2 / 3 O 3-y N y XRD pattern of 0.7BaTaO2N powder, b represents 0.3BaMg. 1 / 3 Ta 2 / 3 O 3-y N y -0.7BaTaO2N powder UV-Vis absorption spectrum;

[0035] Figure 5 Example 1 shows 0.6 BaMg loaded with 1 wt% Pt. 1 / 3 Ta 2 / 3 O 3-y N y -0.4BaTaO2N photocatalytic water splitting hydrogen production activity diagram;

[0036] Figure 6 Example 2 shows 0.6BaMg loaded with 1.5wt% Pt content. 1 / 3 Ta 2 / 3 O 3-y N y -0.4BaTaO2N "Z" mechanism photocatalytic water splitting activity diagram. Detailed Implementation

[0037] The present invention will now be described in detail with reference to examples and accompanying drawings, but the embodiments of the present invention are not limited thereto.

[0038] Example 1

[0039] (1) To synthesize the oxide precursor, TaCl5 was dissolved in methanol, and ethylene glycol and citric acid were added respectively (the molar ratio of TaCl5, ethylene glycol and citric acid was 1:15:60). After complete dissolution, a certain amount of Mg(NO3)2·6H2O and Ba(NO3)2 (the molar ratio of Mg, Ba and Ta was 3:10:7) were added. After the solution became transparent, it was heated until the temperature reached 180℃. It was refluxed for 6 hours to form a polymer gel. The organic solvent was further heated to evaporate to 350℃ and maintained at this temperature for 2 hours for sol-gelling. The resulting powder was then transferred to a ceramic crucible and placed in a muffle furnace for decarbonization. It was then calcined in air at 550℃ for 2 hours. The process was repeated twice to obtain the oxide precursor.

[0040] (2) Nitrogenation pipeline connection: Take a certain amount of precursor oxide powder and place it in a quartz basket padded with quartz wool. Place the basket in the center of the quartz tube. Connect the air inlet of the quartz tube to the gas path containing ammonia and connect the air outlet to the tail gas absorption device.

[0041] (3) Nitriding yielded 0.9 BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.1BaTaO2N, ammonia gas is introduced into the pipeline at a flow rate of 250 ml / min, and the mixture is purged at room temperature for 0.5 h to remove air. Then, the temperature is increased from room temperature to 950℃ at a rate of 5℃ / min, and nitrided at 950℃ for 10 h. The mixture is then cooled to room temperature to obtain a nitrogen-containing compound solid solution powder.

[0042] (4) Supported catalyst, 0.2 g 0.9 BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.1 BaTaO2N powder was impregnated in a chloroplatinic acid solution containing 0.5 wt% Pt, ultrasonically dispersed, evaporated to dryness in a water bath, and then reduced at 200°C for 1 h under a mixed gas flow of hydrogen and argon.

[0043] Example 2

[0044] (1) To synthesize the oxide precursor, TaCl5 was dissolved in methanol, and ethylene glycol and citric acid were added respectively (the molar ratio of TaCl5, ethylene glycol and citric acid was 1:15:60). After complete dissolution, a certain amount of Mg(NO3)2·6H2O and Ba(NO3)2 (the molar ratio of Mg, Ba and Ta was 1:4:3) were added. After the solution became transparent, it was heated until the temperature reached 180℃. The solution was refluxed for 6 hours to form a polymer gel. The organic solvent was further heated to evaporate to 350℃ and maintained at this temperature for 2 hours for sol-gelling. The resulting powder was then transferred to a ceramic crucible and placed in a muffle furnace for decarbonization. The powder was calcined in air at 550℃ for 2 hours. The process was repeated twice to obtain the oxide precursor.

[0045] (2) Nitrogenation pipeline connection: Take a certain amount of precursor oxide powder and place it in a quartz basket padded with quartz wool. Place the basket in the center of the quartz tube. Connect the air inlet of the quartz tube to the gas path containing ammonia and connect the air outlet to the tail gas absorption device.

[0046] (3) Nitriding yielded 0.75BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.25BaTaO2N, ammonia gas is introduced into the pipeline at a flow rate of 250 ml / min, and the mixture is purged at room temperature for 0.5 h to remove air. Then the temperature is increased from room temperature to 950℃ at a rate of 5℃ / min, and nitrided at 950℃ for 10 h. The mixture is then cooled to room temperature to obtain a nitrogen-containing compound solid solution powder.

[0047] (4) Supported catalyst, 0.2g 0.75BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.25BaTaO2N powder was impregnated in a chloroplatinic acid solution containing 0.5wt%Pt, ultrasonically dispersed, evaporated to dryness in a water bath, and then reduced at 200℃ for 1 hour under a mixed gas flow of hydrogen and argon.

[0048] Example 3

[0049] (1) To synthesize the oxide precursor, TaCl5 was dissolved in methanol, and ethylene glycol and citric acid were added separately (the molar ratio of TaCl5, ethylene glycol and citric acid was 1:15:60). After complete dissolution, a certain amount of Mg(NO3)2·6H2O and Ba(NO3)2 (the molar ratio of Mg, Ba and Ta was 1:5:4) were added. After the solution became transparent, it was heated until the temperature reached 180℃. The solution was refluxed for 6 hours to form a polymer gel. The organic solvent was further heated to evaporate to 350℃ and maintained at this temperature for 2 hours for sol-gelling. The resulting powder was then transferred to a ceramic crucible and placed in a muffle furnace for decarbonization. The powder was calcined in air at 550℃ for 2 hours. This process was repeated twice to obtain the oxide precursor.

[0050] (2) Nitrogenation pipeline connection: Take a certain amount of precursor oxide powder and place it in a quartz basket padded with quartz wool. Place the basket in the center of the quartz tube. Connect the air inlet of the quartz tube to the gas path containing ammonia and connect the air outlet to the tail gas absorption device.

[0051] (3) Nitriding yielded 0.6BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.4BaTaO2N, ammonia gas is introduced into the pipeline at a flow rate of 250 ml / min, and the mixture is purged at room temperature for 0.5 h to remove air. Then, the temperature is increased from room temperature to 950℃ at a rate of 5℃ / min, and nitrided at 950℃ for 10 h. The mixture is then cooled to room temperature to obtain a nitrogen-containing compound solid solution powder.

[0052] (4) Supported catalyst, 0.6 g 0.8 BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.4BaTaO2N powder was impregnated in a chloroplatinic acid solution containing 0.5wt%Pt, ultrasonically dispersed, evaporated to dryness in a water bath, and then reduced at 200℃ for 1 hour under a mixed gas flow of hydrogen and argon.

[0053] Example 4

[0054] (1) To synthesize the oxide precursor, TaCl5 was dissolved in methanol, and ethylene glycol and citric acid were added respectively (the molar ratio of TaCl5, ethylene glycol and citric acid was 1:15:60). After complete dissolution, a certain amount of Mg(NO3)2·6H2O and Ba(NO3)2 (the molar ratio of Mg, Ba and Ta was 1:10:9) were added. After the solution became transparent, it was heated until the temperature reached 180℃. The solution was refluxed for 6 hours to form a polymer gel. The organic solvent was further heated to evaporate to 350℃ and maintained at this temperature for 2 hours for sol-gelling. The resulting powder was then transferred to a ceramic crucible and placed in a muffle furnace for decarbonization. The powder was calcined in air at 550℃ for 2 hours. This process was repeated twice to obtain the oxide precursor.

[0055] (2) Nitrogenation pipeline connection: Take a certain amount of precursor oxide powder and place it in a quartz basket padded with quartz wool. Place the basket in the center of the quartz tube. Connect the air inlet of the quartz tube to the gas path containing ammonia and connect the air outlet to the tail gas absorption device.

[0056] (3) Nitriding yielded 0.3BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.7BaTaO2N, ammonia gas is introduced into the pipeline at a flow rate of 250 ml / min, and the mixture is purged at room temperature for 0.5 h to remove air. Then the temperature is increased from room temperature to 950℃ at a rate of 5℃ / min, and nitrided at 950℃ for 10 h. The mixture is then cooled to room temperature to obtain a nitrogen-containing compound solid solution powder.

[0057] (4) Supported catalyst, 0.2g 0.3BaMg 1 / 3 Ta 2 / 3 O 3-y N y -0.7BaTaO2N powder was impregnated in a chloroplatinic acid solution containing 0.5wt%Pt, ultrasonically dispersed, evaporated to dryness in a water bath, and then reduced at 200℃ for 1 hour under a mixed gas flow of hydrogen and argon.

[0058] Figure 1 (a) Sample 0.9 BaMg from Example 1 1 / 3 Ta 2 / 3 O 3-y N y The powder XRD pattern of -0.1 BaTaO2N confirmed that BaMg was obtained after nitriding. 1 / 3 Ta 2 / 3 O 3-y N y Solid solution with BaTaO2N; Figure 1 (b) Sample 0.9 BaMg from Example 1 1 / 3 Ta2 / 3 O 3-y N y The UV-Vis absorption spectrum of -0.1 BaTaO2N shows that the absorption band edge of Example 1 is 550 nm.

[0059] Figure 2 (a) Sample 0.75 BaMg from Example 2 1 / 3 Ta 2 / 3 O 3-y N y The powder XRD pattern of -0.25BaTaO2N confirmed that BaMg was obtained after nitriding. 1 / 3 Ta 2 / 3 O 3-y N y Solid solution with BaTaO2N; Figure 2 (b) Sample 0.75 BaMg from Example 2 1 / 3 Ta 2 / 3 O 3-y N y The UV-Vis absorption spectrum of -0.25BaTaO2N shows that the absorption band edge of Example 2 is 575nm.

[0060] Figure 3 (a) Sample 0.6 BaMg from Example 3 1 / 3 Ta 2 / 3 O 3-y N y The powder XRD pattern of -0.4BaTaO2N confirmed that BaMg was obtained after nitriding. 1 / 3 Ta 2 / 3 O 3-y N y Solid solution with BaTaO2N; Figure 3 (b) Sample 0.6 BaMg from Example 3 1 / 3 Ta 2 / 3 O 3-y N y The UV-Vis absorption spectrum of -0.6BaTaO2N shows that the absorption band edge of Example 3 is 600nm; Figure 3 (c) Sample 0.6 BaMg from Example 3 1 / 3 Ta 2 / 3 O 3-y N y The scanning electron microscope image of -0.4 BaTaO2N shows the morphology of Example 3, which is composed of nanoparticles of approximately 50 to 200 nm in size.

[0061] Figure 4 (a) Sample 0.3 BaMg from Example 4 1 / 3 Ta 2 / 3O 3-y N y The powder XRD pattern of -0.7BaTaO2N confirmed that BaMg was obtained after nitriding. 1 / 3 Ta 2 / 3 O 3-y N y Solid solution with BaTaO2N; Figure 4 (b) Sample 0.3 BaMg from Example 4 1 / 3 Ta 2 / 3 O 3-y N y The UV-Vis absorption spectrum of -0.7BaTaO2N shows that the absorption band edge of Example 4 is 650 nm.

[0062] Application Example 1

[0063] The photocatalytic water splitting reaction to produce hydrogen was carried out in a photocatalytic reactor with an online detection system. The reaction temperature was kept constant at 15°C. The reaction was carried out by top irradiation with a xenon lamp light source. 150 mg of the photocatalyst prepared in Example 3 was ultrasonically dispersed in 150 mL of solution (containing 120 mL H2O and 30 mL CH3OH). Before irradiation, the system was evacuated to remove air. The ultraviolet light was filtered out by a filter (λ≥420 nm). The hydrogen production activity of the photocatalyst under visible light was tested.

[0064] Application Example 2

[0065] The photocatalytic "Z" mechanism water splitting reaction was carried out in a photocatalytic reactor equipped with an online detection system. The reaction temperature was kept constant at 15°C, and the reaction was carried out by top irradiation with a xenon lamp light source. 75 mg of the photocatalyst prepared in Example 3 was ultrasonically dispersed in 150 mL of a solution containing 1 mol / L NaI and 75 mg of PtO. x Before irradiation, the system was evacuated to remove air, and ultraviolet light was filtered out by a filter (λ≥420nm) to test the hydrogen production activity of the photocatalyst under visible light.

[0066] Figure 5 and Figure 6 The photocatalytic activity diagrams for Application Examples 1-2 illustrate how this type of catalyst can be applied to multiple reactions in photocatalysis.

Claims

1. The application of a nitrogen-containing compound solid solution photocatalyst in the photocatalytic "Z" mechanism of total water splitting reaction, characterized in that the preparation method of the nitrogen-containing compound solid solution photocatalyst includes the following steps: (1) Dissolve TaCl5 in methanol solution, add ethylene glycol and citric acid, and make both fully dissolved; (2) Add Ba(NO3)3 and MgCO3 to the transparent solution obtained in step (1) and let them dissolve completely; (3) Heat the solution obtained in step (2) under reflux; (4) Heat the solution obtained in step (3) to perform sol-gelation; (5) The solid powder obtained in step (4) is calcined to remove organic carbon and obtain an oxide precursor. (6) The oxide precursor obtained in step (5) is subjected to nitriding treatment under an ammonia atmosphere to obtain a nitrogen-containing compound solid solution; (7) The nitrogen-containing compound solid solution obtained in step (6) is loaded with noble metal to obtain a perovskite-structured nitrogen-containing compound solid solution photocatalyst; In step (1), the molar ratio of TaCl5, ethylene glycol and citric acid is 1:15:

60. In step (2), the molar ratio of Ba(NO3)3, MgCO3 and TaCl5 is 5:1:

4.

2. The application according to claim 1, characterized in that, In step (3), the reflux temperature is 100~200 ℃ and the reflux time is 3~10 h.

3. The application according to claim 1, characterized in that, In step (4), the heating temperature is 250~400 ℃ and the heating time is 0.1~2 h.

4. The application according to claim 1, characterized in that, In step (5), the roasting temperature is 500~750 ℃ ​​and the roasting time is 0.5~2 h.

5. The application according to claim 1, characterized in that, In step (6), the heating rate of the nitriding treatment is 5℃ / min, the ammonia flow rate is 100~250 mL / min, the nitriding treatment temperature is 900~950℃, and the time is 6~10 h.

6. The application according to claim 1, characterized in that, In step (7), the precious metal includes at least one of Ru, Rh, Pd, Ag, Ir, Pt, and Au, and the loading of the precious metal is 0.01~5 wt%. The method of carrying precious metals is as follows: (1) Disperse nitrogen-containing compound solid solution powder in a solution containing noble metal precursor, disperse ultrasonically, and then evaporate to dryness in a water bath; (2) Reduce at 100~400 °C for 0.5~3.0 h under a hydrogen gas flow, or calcine at 100~500 °C for 0.5~4.0 h under a nitrogen or argon inert atmosphere.

7. The application according to claim 1, characterized in that: using IO3 - / I - Fe 3+ / 2+ [Fe(CN)6] 3- / 4- One or more of these components are used as redox couples and dispersed together with photocatalyst powder in H2O. When exposed to light, the H2O is decomposed to produce hydrogen and oxygen.